Human rights in the digital era : challenges and opportunities from the United Nations human rights system - Iza, Daniela González (Penerbit Universiti Kebangsaan Malaysia, 2021)
One of the most important changes in our era is the ones promoted by the digital technology, which has meant a challenge in the promotion of human rights. Not only do we talk about the vulnerability to privacy, but also the possible biases of algorithms and other risks that represent potential violations to human rights. International organizations, such as the United Nations, have taken this issue in their hands, although the lack of development of norms regarding digital technology and human rights. The main objective of this paper is to analyze the way the non-conventional and conventional mechanisms of the United Nations Human Rights System have treated this issue. Through a document review, some actions and interpretations made by these will be analyzed, in order to determine some opportunities and challenges in the way the United Nations has approached to this issue.